Low-cost multi-object positioning system with optical sensor fusion - Pashchapur, Ravi Ashok; Chen, Yuxi; Ignatyev, Dmitry (American Institute of Aeronautics and Astronautics (AIAA), 2023)
Indoor position estimation of any moving objects with the aid of integration of multiple sensors such as optical, radio, and ultrasonic is an ongoing field of research. Although, commercial companies like VICON and OptiTrack provides the higher precision indoor positioning by using custom design optical sensors, but not every teaching or research institute can afford them because of the cost metric. To overcome this problem, an affordable low-cost solution for object tracking using multiple low-cost cameras is provided in this paper. The object tracking system introduced in this paper uses cameras to track active markers such as LEDs and estimate the coordinates of these LEDs with less than 0.15 meters of error in all the axes. The VICON camera system setup is used to opt ground truth measurements which later utilized for error estimation of the low-cost object tracking system.